Fog attenuation prediction for optical and infrared waves - Al Naboulsi, Maher; Sizun, Herve´; de Fornel, Fre´de´rique (Optical Engineering, 2004)
The principal disadvantage of using free space optics (FSO) telecommunication systems is the disturbing role played by the atmosphere on light propagation and thus on the channel capacity, availability, and link reliability. The wavelength choice is currently a subject of disagreement among designers and users of FSO equipments. Generally this equipment operates in the visible and the near IR at 690, 780, 850, and 1550 nm. Several authors affirm that equipment working at 1550 nm presents less atmospheric attenuation in the presence of fog and thus better link availability. Others consider that for dense fogs all wavelengths are attenuated in the same way (wavelength independence). Fog attenuation in the visible and IR regions is reviewed from an empirical and theoretical point of view. Laser system performance in the presence of fog (advection and convection) in the 0.4- to 15- m spectral zone is investigated using FASCOD computation. A transmission gain of 42 for a lasercom system working at 780 nm is observed compared to the same system working at 1550 nm. This gain reaches 48 if the same system works at 690 nm. Finally, we propose a fast transmission relationship based on an exact Mie theory calculation valid in the 0.69- to 1.55- m spectral bands. It enables us to predict fog attenuation according to visibility without using heavy computer codes. ©